2018
DOI: 10.21608/asnj.2018.58902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Designed Nursing Guidelines on Minimizing Postoperative Complications for Patients Undergoing Thyroidectomy

Abstract: Background: Thyroidectomy is the surgical removal of a partial or complete thyroid gland in case of hyperthyroidism, thyroid cancer and goiter. The aims of this study: were to eveluate effect of designed nursing guidelines on minimizing postoperative complications for patients undergoing thyroidectomy through the following; 1) assess patients' knowledge and practice about thyroidectomy, 2) design nursing guidelines , 3) evaluate the effect of applying these guidelines on minimizing postoperative complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The current study revealed that; more than half of studied patients were males, illiterate, living in rural area and their age group ranged from more than forty to less than fifty years old, this current study result finding was in line with Dr. KrishanY 2015., (Herode et al, 2016) who conducted the study of incidence of post-operative wound infection in orthopedic surgery in Brazil, and who reported that more than half of the studied patients whose age group ranged from 41-50 age years The present study revealed that; Half of the studied sample were having fracture of upper limb, near half of the studied sample were having fracture of lower limb and ten percent were having diagnoses other than these, this result comes in disagreement with (Tamam, 2016), who conducted the study of prevalence and predisposing factors of compartment syndrome among traumatic patients inAssiut University, Hospital , who found that nearly third of the sample included in their study were having tibial plateau fracture. The present study revealed that; there was a highly statistically significant difference between vital signs and wound infection, this result agree with (Hashem, 2018), who conducted the study of effect of designing nursing guideline on minimizing postoperative complication for patients undergoing thyroidectomy Assiut University, who reported that vital signs are a mechanism to universally communicate a patient's condition and severity of their disease. Regarding body mass index there was a positive correlation between body mass index and wound infection this result agree with (Namba et al, 2013), who conducted the study of risk factors associated with deep surgical site infections after primary total knee arthroplasty, who found that deep surgical site infections (SSIs) after primary total knee arthroplasty had high incidence with large body mass index (BMI) (i.e.…”
Section: Table (8)supporting
confidence: 90%
“…The current study revealed that; more than half of studied patients were males, illiterate, living in rural area and their age group ranged from more than forty to less than fifty years old, this current study result finding was in line with Dr. KrishanY 2015., (Herode et al, 2016) who conducted the study of incidence of post-operative wound infection in orthopedic surgery in Brazil, and who reported that more than half of the studied patients whose age group ranged from 41-50 age years The present study revealed that; Half of the studied sample were having fracture of upper limb, near half of the studied sample were having fracture of lower limb and ten percent were having diagnoses other than these, this result comes in disagreement with (Tamam, 2016), who conducted the study of prevalence and predisposing factors of compartment syndrome among traumatic patients inAssiut University, Hospital , who found that nearly third of the sample included in their study were having tibial plateau fracture. The present study revealed that; there was a highly statistically significant difference between vital signs and wound infection, this result agree with (Hashem, 2018), who conducted the study of effect of designing nursing guideline on minimizing postoperative complication for patients undergoing thyroidectomy Assiut University, who reported that vital signs are a mechanism to universally communicate a patient's condition and severity of their disease. Regarding body mass index there was a positive correlation between body mass index and wound infection this result agree with (Namba et al, 2013), who conducted the study of risk factors associated with deep surgical site infections after primary total knee arthroplasty, who found that deep surgical site infections (SSIs) after primary total knee arthroplasty had high incidence with large body mass index (BMI) (i.e.…”
Section: Table (8)supporting
confidence: 90%
“…Control of postoperative complications and minimizing the hospital stay are the most challenging issues that surgeons face all over the world (10) .…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended for benign symptomatic conditions that produce compression symptoms such as cough and dyspnea [4] . The options for surgical management of various thyroid diseases include: total thyroidectomy, subtotal thyroidectomy, in which bilateral small thyroid remnants are left, and thyroid lobectomy; which involves removing the affected part [5] . Every surgical procedure with the inclusion of thyroidectomy has the possibility of complications [6] .…”
mentioning
confidence: 99%